A Novel Approach for Searchable Keyword in Cloud Computing Using Efficient Algorithm - Sai Sirisha, P; Praveen Kumar, K; Vardhan, M Harsha; Karthik, J (International Journal of Computer Sciences and Engineering, 2025)
In ancient, dynamic secret writing systems it provides solely information confidentiality, however, it's incompatible with dynamic multi-keyword over encrypted information by causing secret keys to the user through the mail. In traditional we'll be going to be operative on plain information however in our project we tend to encrypt the information. The info by generating secret keys and activity search on encrypted data by user request. During this paper, we tend to propose a dynamic multi-keyword hierarchical search theme over encrypted cloud information, that at the same time supports dynamic update operations like deletion and insertion of documents. Intensive experiments area unit conducted to demonstrate the potency of the projected theme.